Strengthening Al-Qur’an Writing Skills (Imla’) at The Partner’s Boarding School - Muhammad Sholeh; Zuri Pamuji (Proceeding of Saizu International Conference on Transdisciplinary Religious Studies, 2022)
Every student at UIN Prof.KH. Saifuddin Zuhri is required to have the skills to read and write the Qur’an and the Practice of Worship (BTA-PPI). For each student, the level of competence for these skills will be tested specifically by a team determined by the director of Ma’had Al-Jami’ah. Based on data from Ma’had Al-Jami’ah, writing skills are skills that have a fairly low graduation rate, so it is necessary to make various efforts so that the level of writing skills for students is increased and better. Based on this, this study aims to describe in depth the strategies and efforts of one of the partner boarding schools of UIN Prof. K.H. Saifuddin Zuhri Purwokerto in teaching BTA-PPI skills, especially the skills in writing the Qur’an. This is field research with the descriptive qualitative method and uses interviews, documentation, and observation to find the data. The study results show that the partner boarding schools studied made various efforts to teach BTA-PPI skills, which were adjusted to the standards of Ma’had Al-Jami’ah. So students who live in the boarding school are intensively guided and directed to master BTA-PPI skills, especially the skills on writing the Qur’an.